Pengaruh Biaya Produksi, Persediaan, dan Penjualan terhadap Laba Bersih pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024 - Yulita Sari; Maya Richmayati; Khadijah Khadijah; Andi Aulia Ramadhani; Ita Mustika (ARZUSIN, 2026)
This study was motivated by the importance of understanding the factors that affect the net profit of manufacturing companies, particularly production costs, inventory, and sales, as a basis for making more effective financial decisions. This study aims to examine the effect of production costs, inventory, and sales on net profit in manufacturing companies listed on the Indonesia Stock Exchange in 2021. This study used a quantitative approach with a survey design, involving 40 companies selected through purposive sampling. Data were collected from annual financial statements and analyzed using multiple linear regression with the assistance of SPSS 25. The results showed that production costs had a significant effect on net profit (t = 3.498; significance = 0.001), whereas inventory (t = -0.052; significance = 0.959) and sales (t = 0.636; significance = 0.529) had no significant effect. Simultaneously, the three variables had a significant effect on net profit (F = 22.385; significance = 0.000). The Adjusted R Square value of 0.622 indicates that 62.2% of the variation in net profit can be explained by production costs, inventory, and sales. This study concludes that production costs are the most determining variable affecting net profit; therefore, companies need to prioritize more effective production cost management to improve financial performance.